Has income inequality spiked in Germany? - Markus M. Grabka; Jan Goebel; Jürgen Schupp (DIW Economic Bulletin, 2012)
New analyses of personal income distribution in Germany, based on data from the German Socio-Economic Panel (SOEP), show that real market income in private households rose significantly from 2005 to 2010. An increase in real disposable income was also observed. At the same time, income inequality decreased in both western and eastern Germany. However, the latter showed a further spread at the lower end of disposable income distribution. In the course of this development, the poverty risk in western Germany fell slightly from 2009 to 2010, while it remained unchanged in the eastern part of the country.
Keywords: D31; I31; I32; 330; income inequality; poverty risk; SOEP